Allium muratozelii (Amaryllidaceae), a new species from Turkey - Armağan, Meti̇n (Phytotaxa, 2021)
Allium muratozelii is described here as a new species. Diagnostic morphological characters, a full description, and detailed illustrations are given. Allium muratozelii is known from Tunceli province in eastern Anatolia, Turkey. According to its morphological features, the new species belongs to Allium subg. Melanocrommyum sect. Melanocrommyum. It is distinguished from the morphologically similar A. colchicifolium mainly by scape and leaf length, leaf shape, margins of tepal, and filament color. IUCN red list category, notes on biogeography and ecology of the new species are also given.